Flowering, post-pollination development and propagation of Ebolo (crassocephalum crepidioides (benth.) S. Moore) in Ile-Ife, Nigeria (Journal of Science and Technology, 2016)
A study of Crassocephalum crepidioides, a green leafy vegetable mainly collected from the wild in Nigeria and other parts of Africa, was conducted in order to elucidate flowering, postpollination developments, seed production and germination potential of the plant and investigate the eligibility of other propagation methods. From the flowering studies, it was discovered that peripheral florets opened and were pollinated before central florets. The species had appropriate or good pollination period, however, there might not be sufficient pollens for pollination. The post-pollination period for the maturity of the developing fruits/achenes was observed to be short leading to the production of many immature and malformed fruits or achenes. Partial reflexing and no reflexing of the receptacle were observed to be hindering adequate fruit dispersal. Crassocephalum crepidioides produced up to 768-1152 seeds per plant indicating that the seed production potential of the plant is very high. Germination percentage was not consistent with age and may be influenced by seed maturity. Seeds are photoblastic and germination was promoted by soaking in water. Vegetative propagation was hindered by floral initiation.